2018
DOI: 10.2134/agronj2017.07.0392
|View full text |Cite
|
Sign up to set email alerts
|

Acute High Temperature Response in Wheat

Abstract: Heat waves have a significant impact on crop production and quality of many staple grains including wheat. Under climate change, changing weather patterns including greater temperature volatility are also likely to further affect yield stability. Simulation modeling provides a powerful tool to investigate the interactive effects of abiotic factors and develop adaptive strategies; however, many of these models do not adequately account for the step change response to high temperature occurring during the crop r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…temperature occur, yield potential in wheat is decreased by a more or less a fixed extent. The results of this experiment also support the findings of Nuttall et al [31] who observed that the application of 4-days of cumulative exposure to a high p.a. temperature treatment of 35/ 15°C from 2daa for 6 h per day resulted in 15% reduction in individual grain weight in cv.…”
Section: Discussionsupporting
confidence: 91%
“…temperature occur, yield potential in wheat is decreased by a more or less a fixed extent. The results of this experiment also support the findings of Nuttall et al [31] who observed that the application of 4-days of cumulative exposure to a high p.a. temperature treatment of 35/ 15°C from 2daa for 6 h per day resulted in 15% reduction in individual grain weight in cv.…”
Section: Discussionsupporting
confidence: 91%
“…Ninety-six square pots were prepared with a topsoil (5-15 cm) of a grey Vertosol soil, with preparation according to Nuttall et al (2018). Briefly, soil was air-dried (408C for 4 days) and packed in large sealed square pots (160 mm wide by 160 mm deep by 240 mm high) at 5500 g soil pot -1 , which equated to a bulk density of 1.15 Mg m -3 .…”
Section: Expt 1: High Temperature and Water Availabilitymentioning
confidence: 99%
“…To account for different high-temperature scenarios (temperature and duration) across the two experiments, we used a calculation of heat load that combines the duration and temperature data together to determine the heat stress or load applied to the plant. For Expts 1 and 2, heat load was calculated as a sum of degrees Celsius (8C) above the threshold value (328C) for the logged temperature data (5-min intervals), expressed as degree-hours (8C.h), to which the plant was exposed over the duration of the high-temperature treatment (as per Nuttall et al 2018). The cumulative heat load calculated included any occasion when the temperature within the polyhouse (Expt 1) or glasshouse (Expt 2) exceeded 328C during the growing period.…”
Section: Heat Loadsmentioning
confidence: 99%
“…High temperature conditions also contribute to an overall negative effect on grain filling and physiological maturity. Wheat crop exposed to temperatures above 34 C after the anthesis stage has a significantly low yield due to accelerated senescence, decreased rate and duration of grain filling [25,26], and reduction in grain weight [27]. By quantifying the number of days with temperatures above 35 C in March, which are critical for the grain filling and maturity, we found that the frequency of extreme temperature was relatively high during 2000-2010 ( Figure 2d).…”
Section: Temperaturementioning
confidence: 94%